PERAN GURU PROFESIONAL DALAM MENERAPKAN PERMAINAN TRADISIONAL PADA ANAK USIA DINI - Berkati Bu’ulolo; Yabes Yohanes Zebua (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
Teachers play a central role in realizing effective teaching and learning activities, with the hope of bringing positive changes to students. With the awareness that each student has diverse abilities and characteristics, teachers need to recognize and understand the characteristics of each student to create a conducive and enjoyable learning atmosphere. The purpose of this research is to provide a professional teacher's understanding in applying traditional games in early childhood. This research method uses descriptive qualitative methods with data review from case studies, literature studies, and books as reference references. The results of this study are that teachers play a very important role in traditional games such as teachers as facilitators, introduction to local culture, formation of social skills, improvement of gross and fine motor skills, learning values, development of cognitive abilities, stimulation of creativity: Evaluation and Feedback.